Molecular electronics commercial insights, chemistry, devices, architecture, and programming - Tour, James M. (World Scientific Pub. Co., 2003)
This book presents an in-depth discussion on molecular electronics in an easy-to-understand manner, aiming at chemists, computer scientists, surface scientists, physicists, and applied mathematicians. Lighter overviews are provided for the science-minded layperson and the high tech entrepreneur in this nanoscale science. The author has included a detailed synthetic chemistry treasure chest, protocols of self-assembling routes for bottom-up fabrication atop silicon platforms, representative current-voltage and memory readouts from molecular devices, and overviews of present architectural and mathematical approaches to programming molecular computing machines. The investment and commercial insertion landscape is painted along with a "Who's Who" in the molecular electronics business space. Advice and forewarnings are provided in a practical yet witty manner for the aspiring academic corporate founder and the business CEO wannabe seeking to establish a high tech company while wading through the idiosyncratic morass of university personalities and university-owned intellectual property